Diversity and community structure of soil microarthrophods of several moorlands in Gumukmas District, Jember Regency, East Java - Yanuwiadi, Bagyo; Penatagama, Zulfaidah; Leksono, Amin Setyo; Rahayu, Puji; Nurrofik, Agus; Kurniawan, Nia (Jurnal Biolokus : Jurnal Penelitian Pendidikan Biologi dan Biologi, 2023)
The effectiveness of soil microarthropods as a bioindicator was studied to evaluate various soils in the conditions of various lands, including moorland in Gumukmas District, Jember Regency. This study focuses on data collection of the diversity and structure of soil microarthropod communities along with the assessment of their ecological parameters. Field observations were carried out in five villages in Gumukmas District from August-September 2022 using the hand sorting method.  The data were analyzed using α-diversity parameters (Dominance Index, Simpson Index, Evenness, Shannon-Weiner Index, Brillouin Index, and Margalef Species Richness). Habitat similarities were presented by UPGMA multivariate analysis and the estimation of abiotic factors that influence soil microarthropod composition was estimated by Canonical Component Analysis (CCA). The observations showed a total of 24 families from 13 soil microarthropod orders that spread across Gumukmas District. The abundance of diversity based on the α-diversity is still relatively low to moderate, nevertheless, the correlation of microarthropod orders to environmental factors can reveal conditions of the soil cycle through the study site. The results of the study are expected to assist in efforts to restore the diversity of soil microarthropods to support better soil quality.